Teratogenic effect of Lippia citriodora leaves aqueous extract in mice - Zahra Oskouei Shirvan; Leila Etemad; Reza Zafari; Seyed Adel Moallem; Naser Vahdati-Mashhadian; Hossein Hosseinzadeh (Mashhad University of Medical Sciences, 2016)
Objective: Safety of Lippia citriodora, as a herbal remedy, in pregnancy has not yet been evaluated. This study aimed to identify the effect of L. citriodora aqueous extract on pregnancy outcome in mice. Materials and Methods: Timed-pregnant mice received doses of 0.5 g/kg/day L. citriodora aqueous extract or the vehicle control during organogenesis, intraperitoneally. Maternal body weights were measured throughout the pregnancy. The litters were examined for external malformations and skeletal abnormalities. Fetuses were stained with Alizarin red S and Alcian blue. Results: There were no significant differences in mean maternal weight gain during pregnancy between groups. Also, no significant differences were observed in mean number of implantation, live and resorbed fetuses between control and treated groups. The prevalence of all types of deformity was low and similar to control group (%1.11). Conclusion: The results of this study show that moderate consumption of L. citriodora as an infusion or tea appears to be safe to be used during pregnancy and does not have toxic effects on development of mouse embryo.